Optimization of the Sample Preparation Procedure for the Determination of Trace Elements in Auricularia auricula by Inductively Coupled Plasma-Optical Emission Spectrometry. (24th July 2018) - Li, Ziwei; Han, Dongming; Wang, Mingchuan; Zhang, Yuexin; Wang, Yang; Yan, Xiufeng; Pang, Qiuying
ABSTRACT: This study aimed to develop a precise and accurate method of sample preparation of Auricularia auricula for inductively coupled plasma-optical emission spectrometry-based trace element determination and to compare concentrations of seven trace elements (Mg, Fe, Mn, Zn, Ni, Cr, Sr) in six A. auricula samples belonging to three varieties with two cultivation substrates. Five sample preparation procedures, microwave-assisted digestion, nitric acid digestion with hot plate heating, nitric acid and perchloric acid digestion with hot plate heating, nitric acid digestion with ash content, and aqua regia digestion with ash content, were compared. The performance of the procedures was determined based on the precision and accuracy of the results and the limits of detection of the elements. The best results, with limits of detection of 0.60–6.60 ng · mL −1 and recoveries for spiked samples between 93.80 and 105.00%, were found using nitric acid digestion with ash content. Six A. auricula samples were analyzed using the proposed procedure. Among the tested elements, the concentration of Fe was highest in all six A. auricula samples up to a maximum concentration of 284.83 µg · g −1 . The concentrations of Mn, Cu, and Ni increased in mixed stands (basswood, birch, and mongolica) compared with pine sawdust cultivation.